STRATEGI GURU PENDIDIKAN AGAMA ISLAM MENGGUNAKAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS V DI SDN 23 SAYANG KECAMATAN TELUK KERAMAT TAHUN PELAJARAN 2022/2023 - Puput Ariyanti; Arnadi Arnadi; Syaifudin Syaifudin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The purpose of this study is to describe about; 1) learning planning in the use of audio-visual media to improve the learning activities of grade V students at SDN 23 Sayang for the 2022/2023 Academic Year. 2) The implementation of learning in the use of audio-visual media to increase the learning activities of grade V students at SDN 23 Sayang for the 2022/2023 Academic Year. 3) Evaluation of learning in the use of audio-visual media to improve the learning activities of grade V students at SDN 23 Sayang for the 2022/2023 Academic Year. This study uses a qualitative approach with a descriptive type of research. Data collection techniques use interviews, observations, and documentation. The data analysis techniques used are data reduction, data display , verification and conclusion drawn. The data validity checking techniques used are triangulation and member checks. The results of this study show that; 1) The learning plan in the use of audio-visual media to improve the learning activities of grade V students at SDN 23 Sayang is that PAI teachers prepare lesson plans, and the supporting facilities are infocus, speakers, and laptops. Compatibility between learning media and learning materials. 2) The implementation of learning in the use of audio-visual media to improve the learning activities of grade V students at SDN 23 Sayang, namely conducting apersepi first and in the learning process of teachers using based learning methods, discussion methods, and question and answer methods. 3) Evaluation of learning in the use of audio- visual media to improve the learning activities of grade V students at SDN 23 Sayang, namely in the preparation of evaluation instruments looking at 3 aspects, namely the cognitive, affective, and psychomotor. Furthermore, there are 2 types of evaluations used, namely formative and summative evaluations